An Atypical Anomalous Aortic Origin of the Left Coronary Artery With Intra-Arterial Wall Course Pretending a Normal Migration on Imaging Screening: A Case Report - Hu, Fan; Wang, Xinyue; Wan, Jiaojiao; Li, Yifei; Wang, Tao; Zhou, Kaiyu; Shi, Xiaoqing; Liu, Zhongqiang; Fang, Jie; Hua, Yimin (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND An anomalous aortic origin of a coronary artery (AAOCA) has been considered as a dominant cause of sudden cardiac death (SCD) among young age children. Therefore, it is critical to identify AAOCA timely to avoid lethal events. Recently, accumulating cases of right or left coronary arteries originating from inappropriate locations at the sinus of Valsalva have been identified. Here, we report a rare case of AAOCA with an intra-arterial wall course pretending normal migration on imaging screening in a patient who suffered from syncope. CASE SUMMARY A 7-year-old male without a previous history of cardiovascular and cerebrovascular diseases suddenly suffered from sharp chest pain and syncope after intensive exercise. The electrocardiogram showed that the ST segment of multiple leads was depressed by more than 0.05 mV, and biomarkers indicated severe myocardial injuries. The left ventricular ejection fraction (LVEF) decreased dramatically to 23%. Fulminant myocarditis and cardiomyopathy were therefore excluded. However, a relatively normal coronary artery origin, which arose from the left coronary sinus, presented on echocardiography and cardiac CT angiography (CTA). It is difficult to draw an association between severe clinical manifestations and slight malformations on echocardiography and CTA. Furthermore, selective coronary angiography revealed that an anomalous left coronary artery arose from the superior margin of the inappropriate sinus, developed an intramural wall course and finally exits the left sinus of Valsalva and migrated between the aorta and the pulmonary artery, which induced severe myocardial infarction during exercise. Then, the patient received surgical correction with a modified unroofing procedure. After 2 months of intensive treatment, the patient was discharged and remained asymptomatic through 18 months of follow-up. CONCLUSION AAOCA, especially anomalous left coronary artery (ALCA), represents a major potential risk of SCD. We reported an atypical manifestation of ALCA arising from the inappropriate sinus of Valsalva and merging into the intra-arterial wall to develop a strange course and then sprout between the aorta and the pulmonary artery. The diversity of AAOCA might present as a relatively normal course under noninvasive radiological imaging scanning.